Desarrollo del proceso de atención de enfermería en paciente adulto con colelitiasis - Florencia Murillo, Guillermo Fernando (2019)
The present clinical case is of an adult patient 36 years old who is transferred from the polyclinic of Latacunga to the Hospital de Especialidades FFAA N°1 Quito, is admitted to the emergency area, presents abdominal pain colic type, great intensity 8/10 scale of EVA, located in right hypochondrium with irradiation to epigastrium and right scapular region sign Murphy positive, having as a relation ingestion of fatty food, is accompanied by nausea that does not reach vomiting, there is evidence of algic fascia. Laboratory tests are performed with neutrophilia results without leukocytosis and upper abdominal ultrasound. Liver of usual shape, size and situation, measures 14.8 cm towards the right lobe. No space-occupying lesions in valued segments, undilated intrahepatic bile ducts. Bile ducts of regular borders, wall measures 3.2, with presence of two lithos in its interior, one of them towards vesicular neck, measures 14 and 16 mm respectively, volume of 51.53 cc. With a definitive diagnosis of cholelithiasis. The Nursing Service requests evaluation of general surgery physicians indicates scheduling for surgery. The nurse performs the assessment, patient reports that she has no personal pathological history, but that her grandmother is hypertensive, allergic and surgical records do not refer, the nursing diagnosis is identified with acute pain manifested by expressive behaviors, EVA coded report. Adequate nursing interventions are carried out.